Printing and Publishing Chinese Religion and Philosophy in the Dutch Republic, 1595-1700 The Chinese Imprint - Dijkstra, Trude (Library of the Written Word, 2022)
This book sheds new light on the cultural encounter between China and Europe, by discussing how Chinese religion and philosophy were represented in Dutch printed works between 1595-1700.; Readership: All interested in early modern encounters between Asia and Europe, and anyone concerned with printing and publishing in the seventeenth-century Dutch Republic.